Evaluation cytogenotoxicity of cobalt oxide nanoparticle in mice liver - Amer.I.M; Baiomy A.A; Mansour A.B; Hanan R.H; Attia H.F; Gehan B. A Youssef; Ali.S.A (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
This study was done on 4 groups of mice to evaluate the cytogenotoxicity of cobalt oxide nanoparticles by comet assay from liver tissue and bone marrow to detect DNA damage and the histopathological changes in the hepatic tissues. Significant elevation in %DNA, tail length, and tail moment in liver while in bone marrow the %DNA, tail length, and tail moment showed elevation in 5% cobalt oxide nanoparticles and decline in 10% and 20% of cobalt oxide nanoparticles. The liver tissues of the 5% cobalt nanoparticle group had areas of hepatocellular necrosis, focal aggregations of mononuclear inflammatory cells, and portal congestion, whereas the 10% cobalt oxide nanoparticle group had marked inflammatory cell infiltration, marked vascular congestion, and small focal areas of hepatocellular necrosis that were infiltrated by mononuclear inflammatory cells. The hepatic tissue parenchyma in the 20% cobalt oxide nanoparticles group had clogged blood arteries, and regions of hepatocellular necrosis with mononuclear inflammatory cell infiltration were often seen lesions in the liver. Some liver tissues, however, showed only little improvement. In conclusion the cobalt oxide nanoparticles were showed cytotoxicity and genotoxicity especially in concentration of 5% and 10%.